Wireless Atmospheric Data Logger for a Sensor Network - Usha Sri, P; Narasimha Swamy, B (International Journal of Computer Sciences and Engineering, 2025)
Recording the environmental conditions continuously is a mandatory process in industries. The tracing of the environment parameters leads to the production to continue in a hassle free manner. Using the analogue meters and recording it manually is always a tedious process and non-accurate. Replacing the whole process in a digital manner along with a sophisticated software reduce the time, effort and also produces more accurate results. Embedding sensors, transceivers with microcontroller with reduced power consumption and decreases the tendency of the damage occurrence in the production equipment. Precise monitoring with wireless sensors from a remote site is developed in this project.